Correlations between Leaf Nutrient Content and the Production of Metabolites in Orange Jessamine (Murraya paniculata L. Jack) Fertilized with Chicken Manure - Karimuna, Siti Rahmah; Aziz, Sandra Arifin; Melati, Maya (Journal of Tropical Crop Science, 2015)
Plant secondary metabolites are unique sources for pharmaceuticals and food additives. Orange jessamine (Murraya paniculata) contains secondary metabolite that is beneficial to human health including lowering blood cholesterol levels, anti-obesity, and has the antioxidant capacity. Leaves of orange jessamine have several chemical constituents including L-cadinene, methyl-anthranilate, bisabolene, β-caryophyllene, geraniol, Carene, 5-guaiazulene, osthole, paniculatin, tannins, eugenol, citronelled, coumurrayin and coumarin derivatives. This study aimed to determine the correlation between leaf concentrations of N, P and K with leaf bioactive compounds following chicken manure application to the plants. The experiment was conducted at IPB Experimental Station at Cikarawang, Bogor (6o30' - 6o45' S, 106o30'-106o45' E) from March to November 2014 (250 m above sea level). The study used a randomized block design (RBD) with rates of chicken manure as a treatment, i.e. 0, 2.5, 5 and 7.5 kg per plant. Chicken manure was applied at 30 months after planting (MAP). Leaves were harvested by pruning the plants to a height of 75 cm above the soil surface. The results showed that the optimum rates of chicken manure to produce maximum fresh and dry leaf weight were 3.1 kg and 6.5 kg per plant, respectively. This rate was sufficient for leaf production at the first harvest (34 MAP) but was insufficient for the second harvest (38 MAP). K concentration of the leaves from different positions within the plant and leaf age positively correlated with leaf dry weight (P <0.01), but negatively correlated with total flavonoid content (P <0.01). Leaf P concentration was negatively correlated with dry weight of the 5th young leaves, or mature leaves from all positions. Leaf K concentration was categorized very high (3.59-4.10%), whereas leaf P concentration was high (0.28-0.29%) to very high (0.33-0.35%). The 5th mature leaves determined plant K requirements.Keywords: antioxidant, bioactive compounds, leaf position, organic, NPK leaf concentrations